Aquatic food systems and antimicrobial use in Bangladesh: A One Health perspective - Rheman, Shafiq; Hossain, Sabrina; Khor, Laura; Delamare-Deboutteville, Jerome; Chadag, Vishnumurthy Mohan (WorldFish, 2023)
This scoping review is one of the deliverables of WP3, which reviews past literature and projects on AMU and AMR in the aquatic food systems of Bangladesh from a One Health perspective. The purpose of this review is to gain a better understanding of the challenges of AMU and AMR in the prevailing aquatic food production systems in Bangladesh using a One Health approach. The review also sheds light on past and ongoing initiatives led by government agencies, nongovernmental organizations (NGOs) and collaborative research partners to reduce the burden of AMU and AMR in aquaculture in Bangladesh.